DESIGN OF A WEB-BASED INFORMATION SYSTEM FOR KOMODO AIRPORT - LABUAN BAJO - Sofia Wulandari, Haygia; Suprapto, Yuyun; Chandra Yudho Pranoto, Dani (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
The increasing number of passengers at Komodo Airport – Labuan Bajo demands fast and accessible information services. This study aims to design and develop a website-based information system to facilitate access to airport information for passengers and staff. The research employed a Research and Development (R&D) method using the ADDIE model, which includes analysis, design, development using WordPress CMS, implementation, and evaluation through expert validation and user testing. The validation results showed high feasibility, with scores of 94.67% from IT experts and 95.84% from content experts. Usability testing achieved a score of 77.04%, indicating the system is effective and acceptable for users. The developed website provides comprehensive content such as airport profiles, passenger guides, flight schedules, and local tourism information, accessible across multiple devices. In conclusion, the website-based information system is valid, feasible for implementation, and has the potential to enhance the efficiency of airport information services while supporting the digital promotion of Labuan Bajo as a tourist destination.